Changing the Economics of Organic Waste Disposal Using Managed Ecosystem Fermentation - Calt, Edward A. (International Journal of Biotechnology for Wellness Industries, 2013)
Concentrated organic waste is a major societal problem. It is a disease vector, a source of groundwater contamination, as well as a source of greenhouse gases. Managed Ecosystem Fermentation (MEF) is a technology that converts this societal problem into an economic resource for the community. MEF is a fermentation process that uses over 3,000 species of microbes simultaneously to produce multiple high-value products used in industry and agriculture. The products include fertilizer, high-protein animal feed, volatile fatty acids, longer chain fatty acids, amino acids, enzymes, etc. The values of these products range from $50 to over $16,000 per ton. MEF is an adaptive system that processes non-homogeneous, non-sterile organic waste/s under non-sterile conditions. It converts the waste into industrial products in 24 hours using a microbial system that has worked for millions of years. It is the only known technology that can convert cellulose into protein. Society benefits from converting what is now a cause of disease, groundwater contamination and greenhouse gases into valuable products.